TERRITORIAL DEVELOPMENT IN THE GREEN BELT OF FENNOSCANDIA BASED ON TOURISM ACTIVATION - Дружинин, Павел Васильевич; Шкиперова, Галина Тимофеевна; Курило, Анна Евгеньевна; Druzhinin, Pavel; Shkiperova, Galina; Kurilo, Anna (Trudy Karelʹskogo nauchnogo t͡s︡entra Rossiĭskoĭ akademii nauk, 2019)
Borderland municipalities traversed by the Green Belt of Fennoscandia are facing a difficult socio-economic situation, but nature conservation areas in their territories posses a substantial potential and offer opportunities for tourism development. A systemic integration of the existing possibilities can propel the tourism industry and contribute to sustainable development of the border areas. The research methodology is based on the sustainable development concept. The methods of system, statistical and content analysis were employed for assessments. The background information for the study were open access materials, including materials of the Russian State Statistics Service, strategic documents posted on official websites of Russian regional executive authorities. The article gives recommendations on how to augment the tourist flow to protected areas in the Green Belt of Fennoscandia and expand the range of tourist services. At the moment, the potential of natural areas and sites, which are full-fledged economic entities, is not used to the full. Their greater involvement in economic circulation would help overcome the negative trends in the socio-economic development of border areas. The concept of tourism development, partially described in this article, will improve the consistency of the actions taken by authorities at different levels and the economic entities operating in the Green Belt of Fennoscandia. The results of the study can be applied in the development of strategic planning documents of municipal districts.